Elaborasi Fungsi Supervisi Kepala Sekolah terhadap Penerapan Tugas Pokok dan Fungsi Guru Studi Tindakan Sekolah di SMP Azzainiyyah - Suharyanto H. Soro; Sri Handayani; Iis Farida Zein; Caca Danuwijaya (Journal on Education, 2022)
This research involved 22 teachers at Azzainiyyah Middle School, Sukabumi Regency, and the results of this study clearly proved that the implementation of school principal supervision in schools can improve the implementation of the main tasks and functions of the teacher. The effectiveness of learning will support the main tasks and functions of the teacher. In the preliminary study, it shows that in the field, that the subjects in general in the research are still lacking and not optimal in carrying out their main tasks and functions. Supervision in programs in schools that must be carried out by school principals will have a significant impact on a learning process. teachers in the school environment. The aim of this study was to provide the results of the principal's supervision of the implementation of the main tasks and functions of the teacher through a series of activities in two cycles which were carried out and utilized optimally.